The ethnobotanical notes from Nizip (Gaziantep-Turkey) - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2017)
This paper reports folk medicinal and food plants of Nizip (Gaziantep) located in the south part of Turkey. The purpose of the study is to gather, determine, and record the plants that are used as source of food and medicine by local people. The information was obtained from participants in face to face interviews; furthermore, the specimens of the plants were collected. Voucher specimens were deposited at the Herbarium of the Faculty of Pharmacy, Marmara University. Totally, twenty-seven plants are recorded as used as traditional folk medicine for the region, and thirteen of these are also used as a source of food. Among them, 20 taxa were wild and 7 taxa were cultivated plants. According to the majority of the plants which have similar usage, the plants are mostly used for gastrointestinal, respiratory system diseases and diabetes.
Keywords: Ethnobotany; folk medicinal plants; food plants; Nizip; Turkey; FOLK MEDICINAL-PLANTS; EAST ANATOLIA; ELAZIG-TURKEY; VILLAGES; PROVINCE; TUNCELI; ERZURUM